Sedentary behavior in adolescents: the 11-year follow-up of the 1993 Pelotas (Brazil) birth cohort study Comportamento sedentário em adolescentes: a visita de 11 anos da coorte de nascimentos de Pelotas, Rio Grande do Sul, Brasil, 1993 - Samuel C. Dumith; Pedro C. Hallal; Ana M. B. Menezes; Cora Luiza Araújo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
The aim of this study was to estimate the prevalence of sedentary behavior and investigate associated factors in adolescents 11 years of age from the 1993 birth cohort in Pelotas, Rio Grande do Sul State, Brazil. Sedentary behavior was investigated with a questionnaire, and was defined as spending more than two hours per day watching television, playing videogames, or using the computer. Of the 4,452 adolescents interviewed, 98% reported watching television, 44% playing videogames, and 22% using the computer. The average time spent on each of these electronic media was 197, 36, and 17 minutes per day, respectively. Prevalence of sedentary behavior was 79.7% (95%CI: 78.6; 80.9) and showed a positive association with socioeconomic level and nutritional status and a negative association with well-being. These 11-year-olds spent extensive time at TV viewing, videogames, and the computer. Special attention should be given to the most exposed groups of adolescents, including the more affluent, overweight, and those with limited schooling. O objetivo deste estudo foi determinar a prevalência e investigar os fatores associados ao comportamento sedentário em adolescentes de 11 anos, pertencentes à coorte de nascimentos de 1993 de Pelotas, Rio Grande do Sul, Brasil. O comportamento sedentário foi coletado por meio de questionário, e definido como ficar mais de duas horas por dia assistindo à televisão, jogando videogame ou usando computador. Dos 4.452 adolescentes entrevistados, 98% assistiam à televisão, 44% jogavam videogame e 22% usavam computador. O tempo médio na frente de cada um desses meios eletrônicos foi, respectivamente, 197, 36 e 17 minutos por dia. A prevalência de comportamento sedentário foi de 79,7% (IC95%: 78,6; 80,9), e teve uma associação positiva com nível socioeconômico e com estado nutricional, e negativa com a escala de bem-estar. O tempo despendido em atividades como ver televisão, jogar videogame e usar computador foi elevado (média superior a 4 horas/dia). Maior atenção deve ser dada aos grupos mais expostos, tais como adolescentes de classe alta, acima do peso e com menor nível de bem-estar.